Quasi-Exactly Solvable N-Body Spin Hamiltonians with Short-Range Interaction Potentials - Enciso, A.; Finkel, F.; González-López, A.; Rodríguez, M.A. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
We review some recent results on quasi-exactly solvable spin models presenting near-neighbors interactions. These systems can be understood as cyclic generalizations of the usual Calogero-Sutherland models. A nontrivial modification of the exchange operator formalism is used to obtain several infinite families of eigenfunctions of these models in closed form.